Enhancement of voltage generation for thermoelectric generator using parabolic pulsed heating - Piyapat Panmuang; Chonlatee Photong (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This paper presents the results of investigations of the impact of parabolic pulsed heating on output voltage levels of a thermoelectric generator. The experiment was set up and tested under different test conditions. The output voltage levels were investigated. The experimental results showed that applying parabolic pulsed heating of 40, 60, 80 and 100 °C significantly maintained the output voltage levels of thermoelectric generator at about 80-95% which was different from steady heating case which was about 10-30% of maximum voltage level.  Moreover, the parabolic pulse heating technique allows the heatsink to not be heated continuously and then the high temperature could be released out from a heat exchanger outside the heating period. This causes the next heating period to have a temperature difference between both sides of the device, and for that reason, could provide more power and efficiency.